Surgical Research, Staging-Guided Technical Procedures and Long-Term Clinical Outcomes for the Treatment of Peripheral Lymphedema: the Genoa Protocol - Corrado Cesare Campisi; Lidia Molinari; Caterina Sara Campisi; Giuseppe Villa; Ezio Fulcheri; Corradino Campisi (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
The Author 's vast surgical experience in the treatment of primary and secondary peripheral lymphedema is reported. The objective is to describe the techniques and the long-lasting clinical outcomes based on more than 45 years research and clinical applications, with particular reference to staging-guided derivative and reconstructive lymphatic microsurgery at a single site, and to complementary, sequential, minimally invasive procedures of selective liposuction. 5.046 cases of patients (demographic characteristics are at length described) affected by upper and/or lower limb lymphedema, between 1973 and 2020, underwent lymphatic microsurgery and, between 2012 and 2020, Fibro-Lipo-Lymph-Aspiration according to Lymph Vessel Sparing Procedure (FLLA-LVSP), for latest stages of Lymphedema previously treated by Lymphatic Microsurgery with partial improvement of the disease. Derivative Multiple Lymphatic-Venous Anastomoses (MLVA) or, in selected cases of Phlebolymphedema absolutely contraindicating derivative procedures, lymphatic pathway reconstruction, using interpositioned vein grafted shunts (Multiple-Lymphatic-Venous-Lymphatic Anastomose - MLVLA), above all at lower limbs, were performed at a single site, either the brachial-axillary or inguinal-crural region. Adopted surgical techniques are described in detail. As far as exposition of results is concerned, patients were followed up for a minimum of 5 years to over 20 years. Clinical outcomes included excess limb volume (ELV), frequency of dermatolymphangioadenitis (DLA) attacks, lymphoscintigraphy, and use of conservative therapies. Compared with preoperative conditions, patients obtained significant reduction in ELV of over 90%, with an average follow-up of 10 years or more. Over 96% of patients with earlier stages of disease (stage IB or IIA) progressively stopped using conservative therapies and over 80% of patients with later stages (stages IIB and III) significantly decreased the frequency of physical therapies and discontinued compressive garments or stockings. DLA attacks considerably reduced by over 95%. MLVA or MLVLA techniques when performed at a single site produce excellent outcomes in the treatment of both primary and secondary lymphedemas, giving the possibility of a complete restoration of lymphatic flow in early stages of disease, when tissue changes are minimal. For late stages of lymphedema only partially responding to MLVA or MLVLA, FLLA-LVSP sequential procedures can significantly improve the long-term clinical outcomes.  Staging-guided treatment of peripheral lymphedema, according to Authors' Genoa Protocol, carries out contextual target of primary, secondary and tertiary prevention in the potential worsening of the disease.